Religious pluralism and pragmatist theology : openness and resistance - Henriksen, Jan-Olav, (Currents of Encounter;, 2019)
Inspired by pragmatism, this book addresses religious plurality with the aim of bringing forth how it may be approached constructively by Christian theology. Accordingly, not doctrine, but practices are focussed in its analyses of interreligious topics. Henriksen argues that engagement with the diversity of religious traditions should be grounded in openness towards the other, and resistance against making others similar to oneself. Accordingly, the book presents a theological approach where interaction between religious practitioners is considered a benefit and a necessity for the positive future of religious traditions. It will be of interest to anyone who is interested in the understanding of religious pluralism from the point of view of Christian theology.